2019
DOI: 10.3847/1538-4357/ab2edc
|View full text |Cite
|
Sign up to set email alerts
|

New Hot Subdwarf Stars Identified in Gaia DR2 with LAMOST DR5 Spectra. II.

Abstract: 388 hot subdwarf stars have been identified by using the Hertzsprung-Russell (HR) diagram built from the second data release (DR2) of the Gaia mission. By analyzing their observed LAMOST spectra, we characterized 186 sdB, 73 He-sdOB, 65 sdOB, 45 sdO, 12 He-sdO and 7 He-sdB stars. The atmospheric parameters of these stars (e.g., T eff , log g, log(nHe/nH)) are obtained by fitting the hydrogen (H) and helium (He) line profiles with synthetic spectra calculated from non-Local Thermodynamic Equilibrium (non-LTE) m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 78 publications
7
67
0
Order By: Relevance
“…Two distinct helium sequences, e.g., a He-rich sequence (fitted by dotted line) and a He-weak sequence (fitted by dot-dashed line), which were discovered by Edelmann et al (2003) and confirmed by later studies (Németh et al 2012;Geier et al 2013;Luo et al 2016b;Lei et al 2018Lei et al , 2019b, are clearly present in this panel. As found by Lei et al (2019b), the He-rich sequence consists of sdB, sdOB, He-sdOB and He-sdB stars, while the He-weak sequence consists purely of sdO stars. Furthermore, the 3 He-sdO stars (aqua left triangles) identified in this study are located between the two He sequences.…”
Section: Spectroscopy and Spectral Classificationsupporting
confidence: 72%
See 4 more Smart Citations
“…Two distinct helium sequences, e.g., a He-rich sequence (fitted by dotted line) and a He-weak sequence (fitted by dot-dashed line), which were discovered by Edelmann et al (2003) and confirmed by later studies (Németh et al 2012;Geier et al 2013;Luo et al 2016b;Lei et al 2018Lei et al , 2019b, are clearly present in this panel. As found by Lei et al (2019b), the He-rich sequence consists of sdB, sdOB, He-sdOB and He-sdB stars, while the He-weak sequence consists purely of sdO stars. Furthermore, the 3 He-sdO stars (aqua left triangles) identified in this study are located between the two He sequences.…”
Section: Spectroscopy and Spectral Classificationsupporting
confidence: 72%
“…In panel b, one also can find a gap (e.g., T eff = 40000 K and log(nHe/nH) = 0.0) in He-sdOB stars (red diamonds), which splits the He-sdOB stars into two subgroups, e.g., a subgroup with higher He abundances and temperatures, and the other subgroup with lower He abundance and temperatures. With larger size of He-sdOB stars, this gap is more clearly present in panel b of Fig 4 in Lei et al (2019b). As discussed in Lei et al (2019b), the gap also appears in the EHB stars of GC ω Cen, but the star fraction of the two subgroups between field hot subdwarf stars and ω Cen EHB stars are very different.…”
Section: Spectroscopy and Spectral Classificationmentioning
confidence: 66%
See 3 more Smart Citations